2003
DOI: 10.1007/978-3-540-39903-2_23
|View full text |Cite
|
Sign up to set email alerts
|

A Navigation System for Augmenting Laparoscopic Ultrasound

Abstract: Abstract. Establishing image context is the major difficulty of performing laparoscopic ultrasound. The s tandard techniques u sed by transabdominal ultrasonographers to understand image orientation are difficult to apply with laparoscopic instruments. In this paper, we describe a navigation system that displays the position and orientation of laparoscopic ultrasound images to the operating surgeon in real time. The display technique we developed for showing the orientation information uses a 3D model of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…They found an average localization error of 5.3 mm.  Ellsmere (Ellsmere et al, 2003;Ellsmere et al, 2004): EM tracking, flexible LUS probe, in vivo studies, single point cross wire calibration, and anatomical landmark based registration (CT to LUS). They demonstrated on the development fo a system for orienting and visualizing LUS images better.…”
Section: Literature Overview On Navigated Lusmentioning
confidence: 99%
“…They found an average localization error of 5.3 mm.  Ellsmere (Ellsmere et al, 2003;Ellsmere et al, 2004): EM tracking, flexible LUS probe, in vivo studies, single point cross wire calibration, and anatomical landmark based registration (CT to LUS). They demonstrated on the development fo a system for orienting and visualizing LUS images better.…”
Section: Literature Overview On Navigated Lusmentioning
confidence: 99%
“…Since fast and precise automatic algorithms for non-rigid intraoperative registration of 3D ultrasound data are still under development, for neurosurgery Lindseth et al [6] suggested only to rigidly register preoperative data, trust on ultrasound navigation and use the preoperative data as an orientation aid. Applications in abdominal interventions which make use of preoperative image data to augment navigated intraoperative ultrasound scans include: laparoscopy [7,8] for better orientation and thermal ablation of liver lesions [9,10] for precise placement of preplanned applicator positions. Fast and robust intraoperative registration is the crucial task for augmenting the ultrasound data.…”
Section: Introductionmentioning
confidence: 99%
“…The latest model of MMCS has a small size, only 0.8 mm in diameter and 8 mm in length. The MMCS is used for needle guidance [7], bronchoscopic manipulation [8], and laparoscopic surgery manipulation [9]. The MMCS was compared with other corrective methods through use of a mathematical method by Kindratenko and Bennett [10].…”
Section: Introductionmentioning
confidence: 99%